Pengaruh Promosi, Brand Image, dan Shopping Lifestyle terhadap Impulse Buying di Shopee - Abdul Salam (JESI (Jurnal Ekonomi Syariah Indonesia), 2022)
This study aims to analyze the effect of promotion, brand image and shopping lifestyle on impulse buying at shopee in the Margoluwih Village community. This study uses a quantitative approach with data collection using a questionnaire. The population in this study is the people of Margoluwih Village. The sampling technique was the Slovin formula and the research sample obtained was 97 respondents. There are two variables used in this study, namely the independent variable and the dependent variable. The independent variables in this study were promotion (X1), brand image (X2), and shopping lifestyle (X3). For the dependent variable, namely impulse buying (Y). The method of data analysis with multiple linear regression models, then in processing the data using the Eiews 9 software application. The results of this study based on t-test analysis showed that promotion and shopping lifestyle had a positive effect on impulse buying at shopee. Meanwhile, brand image does not have a positive effect on impulse buying at shopee in the Margoluwih Village community. The coefficient of determination (Adjusted R Square) is 0.634453 or 63%. This means that Promotion (X1), Brand Image (X2), and Shopping Lifestyle (X3) have a joint effect of 63%. While the other 37% are influenced by other factors not mentioned in this study.